Panorama : Italie 78 - Lebel, Robert; Bailly, Jean-Christophe; Parra-Aledo, Marie-José; Domecq, Jean-Philippe; Jouffroy, Alain; Vallier, Dora; Calas, Nicolas; Sergeant, Philippe; Baatsch, Henri-Alexis; Schmied, Wieland; Clay, Julien; Volboudt, Pierre; et al. (Paris : Cahiers, 1978)
Poussin ; Delvaux, Paul ; Hopper, Edward ; Lindner, Richard ; Soulages ; Johns, Jasper ; Erro ; Monory ; De Chirico, Giorgio ; Magnelli, Alberto ; Adami ; Guttuso ; Gentilini, Franco ; Manzù ; Cremonini ; Guadagnucci ; Baruchello ; Carmelo
Cahiers d'art + Chroniques du jour
Lithographie originale de Gentilini
boek
Keywords: De Chirico, Giorgio